Perubahan Kebijakan Luar Negeri Filipina Terhadap China di Bawah Kepemimpinan Presiden Rodrigo Duterte Terhadap China dalam Konflik Laut China Selatan - Damping, Gerald; Windiani, Reni (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
The South China Sea (SCS) issue is a contest of territorial disputes between disputed countries. The Philippines, as one of the countries with an interest in the region, has seen a change in the direction of its foreign policy in dealing with the issue. The current President of the Philippines, Rodrigo Duterte, changed the direction of the Philippines' foreign policy toward China from previously confrontational, to cooperative with China. In this study, these foreign policy changes were analyzed by internal and external factors that made the Philippines have only two (2) options, to submit or to oppose. The concept used in this study is to use the concept of political realism initiated by Thucydides that a strong inclined party can act whatever they want and the weak-leaning party will suffer consequences for the party that tends to be strong and also use internal and external concepts. The type of research used is by qualitative explanative methods with data collection techniques using primary data and secondary data. The results of the study obtained are that there are internal factors such as Rodrigo Duterte's role as President, interest groups, and the Philippine Senate and external factors such as historical claims of the South China Sea region and the state of the international system affecting Philippine foreign policy. Other studies have also shown that there is a link between this change in Philippine foreign policy and the concept of political realism.